Selective Ring‐Opening of Di‐Substituted Epoxides Catalysed by Halohydrin Dehalogenases. Issue 8 (15th March 2019) - Calderini, Elia; Wessel, Julia; Süss, Philipp; Schrepfer, Patrick; Wardenga, Rainer; Schallmey, Anett
Abstract: Halohydrin dehalogenases (HHDHs) are valuable biocatalysts for the synthesis of β‐substituted alcohols based on their epoxide ring‐opening activity with a number of small anionic nucleophiles. In an attempt to further broaden the scope of substrates accepted by these enzymes, a panel of 22 HHDHs was investigated in the conversion of aliphatic and aromatic vicinally di‐substituted trans ‐epoxides using azide as nucleophile. The majority of these HHDHs was able to convert aliphatic methyl‐substituted epoxide substrates to the corresponding azidoalcohols, in some cases even with absolute regioselectivity. HheG from Ilumatobacter coccineus exhibited also high activity towards sterically more demanding di‐substituted epoxides. This further expands the range of β‐substituted alcohols that are accessible by HHDH catalysis. Abstract : More than you think : An unexpected large number of halohydrin dehalogenases (HHDHs) was found to convert non‐terminal epoxide substrates to the corresponding azidoalcohols. Some enzymes displayed even absolute regioselectivity, enabling the preparative‐scale synthesis of regioisomerically pure products. This further expands the range of β‐substituted alcohols that are accessible by HHDH catalysis.